Medical students’ interests on rural practices - Khairinnisa Maizal Gazali; Rizma Syakurah; Mariatul Fadilah (International Journal of Public Health Science (IJPHS), 2019)
Misdistribution of physicians is still an issue, especially physicians’ lack of interest to work in rural area. Finding characteristics from medical students that show interest to work in rural areas is important to craft effective policy to enforce young physicians to work in rural areas. This study was quantitative analytics. Participants rated the influence of 19 factors that affect their interest towards working in rural area using translated and validated questionnaire, distributed online to all medical students from 20 medical faculties in Sumatra. Out of 1124 respondents, 748 (66.5%) subjects interested to work in rural area. Determinants which influence medical students’ interest towards working in rural area are past experience of visiting rural area (p<0.001), careers opportunity (p<0.001), family’s socioeconomic status (p=0.001), proximity to family (p=0.001), rural area’s facilities (p=0.002), culture of rural community (p=0.005), students’ lifestyle (p=0.005), rural curriculum (p=0.007), proximity to spouse (p=0.031) and location of university (p=0.049). Past experience of visiting rural area (OR 2.281, p<0.001) is the most determining factor to influence students’ interest towards working in rural area. Medical students mostly interested to work in rural area. Past experience of visiting rural area was the most influential factor for medical students’ interest on rural practices